Pengaruh Edukasi Gizi Seimbang Terhadap Pencegahan Stunting Pada Keluarga Dengan Balita Stunting Diwilayah Kerja Puskesmas Keperawatan Betungan Kota Bengkulu Tahun 2023 - Agyathien, Meychania; Samidah, Ida; Hidayat, Yance (Universitas Dehasen Bengkulu, 2024)
Based on the Ministry of Health's Indonesian Nutrition Status Survey (SSGI) (2022), the prevalence of stunted toddlers in Indonesia reached 21.6%. Meanwhile, data from the Bengkulu City Health Service shows that out of 10,237 toddlers, 147 toddlers are stunted, whose height and weight are lower than children their age. Based on the conditions above, one form of treatment that can be done is through education about balanced nutrition.This study aims to be able to carry out nursing care and document the results of nursing care for Families of Mr. D and Mr. M with a stunted toddler, by providing health education about balanced nutrition in the working area of Betungan Nursing Health Center in 2023.The method in nursing care is a case study using a descriptive method, namely by using facts according to the data obtained regarding the patient's condition.The results of this study show that in assessing families with stunted toddlers, 1 nursing problem can be established, namely a knowledge deficit. Health education about balanced nutrition can be carried out in the Families of Mr. D and Mr. M with a stunted toddler for 5 days, within 45 minutes of administration, there was an increase in knowledge, in the pre test the client could only answer 1 question out of 5 questions while in the post test the client could answer all the questions correctly.Based on the results of this research, it can be concluded that providing health education about balanced nutrition can increase patient knowledge. It is recommended that community health center officers frequently provide health education therefore people can be exposed to material about stunting and increase their knowledge.